2020
DOI: 10.3390/e22040493
|View full text |Cite
|
Sign up to set email alerts
|

Robust Change Point Test for General Integer-Valued Time Series Models Based on Density Power Divergence

Abstract: In this study, we consider the problem of testing for a parameter change in general integer-valued time series models whose conditional distribution belongs to the one-parameter exponential family when the data are contaminated by outliers. In particular, we use a robust change point test based on density power divergence (DPD) as the objective function of the minimum density power divergence estimator (MDPDE). The results show that under regularity conditions, the limiting null distribution of the DPD-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Moreover, additionally assuming Kim and Lee [ 37 ] showed that the CUSUM test statistics designed for detecting a change in have the limiting null distribution of the sup of a Brownian bridge. In practice, is often harnessed and an optimal can be selected through the method of Warwick [ 39 ] and Warwick and Jones [ 40 ]; see Remark 1 of Kim and Lee [ 36 ].…”
Section: Mdpde For Ingarch Model: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, additionally assuming Kim and Lee [ 37 ] showed that the CUSUM test statistics designed for detecting a change in have the limiting null distribution of the sup of a Brownian bridge. In practice, is often harnessed and an optimal can be selected through the method of Warwick [ 39 ] and Warwick and Jones [ 40 ]; see Remark 1 of Kim and Lee [ 36 ].…”
Section: Mdpde For Ingarch Model: An Overviewmentioning
confidence: 99%
“…In this section, we apply to a real dataset, using the extreme events of the daily log-returns of GS stock from 2 July 2007 to 28 February 2020. Davis and Liu [ 11 ] and Kim and Lee [ 37 ] used the GS stock datasets with different periods, but their works were focused on parameter estimation and the retrospective change point test. For the task of online monitoring, we first calculated the hitting times, for which the log-returns of GS stock fall outside the 0.05 and 0.95 quantiles of the data, and generated the time series of counts , .…”
Section: Real Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the robust estimation methods, we employ the minimum density power divergence estimator (MDPDE) approach that was originally proposed by Basu et al [ 22 ], because it is well known to consistently provide robust estimators in various situations. For previous works in the context of time series of counts, see Kang and Lee [ 23 ], Kim and Lee [ 24 , 25 ], Diop and Kengne [ 26 ], Kim and Lee [ 27 ], and Lee and Kim [ 28 ], who studied the MDPDE for Poisson AR models, zero-inflated Poisson AR models, one-parameter exponential family AR models, and change point tests. For another robust estimation approach in INGARCH models, see Xiong and Zhu [ 29 ] and Li et al [ 30 ], who studied Mallows’ quasi-likelihood method.…”
Section: Introductionmentioning
confidence: 99%
“…A real data analysis of the return times of extreme events of Goldman Sachs Group (GS) stock prices is also provided to illustrate the validity of the proposed test. These authors, see [24], considered the CUSUM tests based on score vectors for the MLE and MDPDE in exponential family distribution INGARCH models.…”
mentioning
confidence: 99%